Towards establishing an Islamic retail bank in a Muslim-minority country: prospects and challenges in Mauritius - Najmul Hussein Rassool (ISRA International Journal of Islamic Finance, 2018)
Purpose: The purpose of this research study is to explore and analyze the factors that will favour or constrain the introduction of an Islamic Retail bank in a Muslim-minority country such as Mauritius. This research attempts to fill the gap in the empirical literature on the setting up of an Islamic Retail bank in a Muslim-minority country. It recognizes upfront that Islamic banking offers an alternative banking system that is attractive to both Muslims and non-Muslims. Design/methodology/approach The research adopts a mixed approach to address the prospects and challenges of establishing an Islamic Retail bank in Mauritius. Findings The research finds that there are various prospects for an Islamic retail bank in Mauritius for Muslims and non-Muslims, including enabling legal, fiscal and regulatory framework, the financing of small- and medium-sized enterprises and the issuance of ṣukūk (Islamic investment certificates). The research also finds that the development of an Islamic retail bank in Mauritius face various challenges. Some of these challenges are lack of Sharīʿah-compliant liquidity instruments and inter-bank deposits, lack of knowledge and understanding of Sharīʿah-compliant products and the enforcement of Islamic contracts in court. Originality/value This in-depth study appears to be comprehensive and will help in developing a solid foundation for establishing an Islamic retail bank in Mauritius.
Keywords: 330; Challenges; Islamic retail banking; Mauritius; Muslim-minority country; Prospects